Grapevine Potassium Nutrition and Fruit Quality in the Context of Climate Change - Villette, Jérémy; Cuéllar, Teresa; Verdeil, Jean-Luc; Delrot, Serge; Gaillard, Isabelle (Frontiers in Plant Science, 2020)
Potassium (K+) nutrition is of relevant interest for winegrowers because it influences grapevine growth, berry composition, as well as must and wine quality. Indeed, wine quality strongly depends on berry composition at harvest. However, K+ content of grape berries increased steadily over the last decades, in part due to climate change. Currently, the properties and qualities of many fruits are also impacted by environment. In grapevine, this disturbs berry properties resulting in unbalanced wines with poor organoleptic quality and low acidity. This requires a better understanding of the molecular basis of K+ accumulation and its control along grape berry development. This mini-review summarizes our current knowledge on K+ nutrition in relation with fruit quality in the context of a changing environment.